Sistem Informasi LFC Digital Printing (Studi Kasus Pemesanan Online) Berbasis Web Pada CV. LFC Multimedia Grafindo - Nazmi, Sandy; Hamid, Abdul (Journal Information Technology Trends (JITRENDS), 2023)
Good service to customers is the main key to success in business competition in the printing sector. By providing good service, customers will feel happy and with good service, of course, customers will always believe in continuing to use the products produced by the company. LFC Digital Printing is a company that serves and is engaged in Digital Printing, Printing, Merchandise, and Advertising. This company gets many online orders every day, especially online orders made by customers who are already members of the company. Ordering online at LFC Digital Printing is still using the Whatsapp chat application, which is quite a hassle because of the many chats from other customers. Based on these problems, it is necessary to create an integrated system from the customer with the LFC Digital printing company, namely "LFC Digital Printing Information System (Online Ordering Case Study) Web-Based on CV. LFC Multimedia Grafindo” in which there is an online ordering feature. So that with this system, it can meet the needs of customer orders more quickly and more efficiently. The author built this system designed using ERD and UML and using the PHP and MySql programming languages ​​as the database.